Design of Rigid Pavement for Oke- Omi Road, Ibadan, Nigeria (2022)
The Paper determined the capacity and level of operational performance of Ojoo Roundabout and New Garage Roundabout traffic intersections in Ibadan, Oyo State, Nigeria. These Roundabouts were gridlock intersections, where roundabout was introduced to control traffic flow and reduce congestion. As traffic volume increases in Ibadan metropolis, the unsignalized road intersections having roundabouts as control measures also exhibit traffic congestion especially at peak periods. This study analyzed the traffic operation and evaluated the capacity for the two selected roundabouts. Geometric data of the roundabouts (entry width, circulatory road width, number of entry and circulatory lanes, and island diameter), traffic movement data with vehicle characteristics and traffic volume data in form of video recordings were collected for the two selected roundabouts at morning and evening peak periods. Empirical analysis technique was adopted to evaluate the capacity for each roundabout. Evaluated results showed that the degree of saturation (DOS) i.e. volume to capacity ratio of 0.78 and 2.49 at morning peak period had equivalent level of service (LOS) of ‘C’ and ‘F’ for Ojoo Roundabout and New Garage Roundabout, respectively. Also, at evening peak period the degree of saturation of 0.84 and 0.75 gave a corresponding level of service of ‘D’ and ‘C’ for Ojoo Roundabout and New Garage Roundabout, respectively. This study showed that the traffic carrying capacity at peak periods for Ojoo roundabout is operating at an acceptable condition both in the morning and evening peak periods. New Garage Roundabout is operating at near capacity at evening peak period, but operating above capacity at morning peak period, which shows that the present conditions are not adequate for controlling traffic operation.